The program risks of work-integrated learning: a study of Australian university lawyers. Issue 1 (2nd January 2018) - Cameron, Craig; Freudenberg, Brett; Giddings, Jeff; Klopper, Christopher
ABSTRACT: Work-integrated learning (WIL) is a risky business in higher education. The strategic opportunities that WIL presents for universities cannot be achieved without taking on unavoidable legal risks. University lawyers are involved with managing the legal risks as part of their internal delivery of legal services to universities. It is important to identify the risks that potentially arise, so these can then be managed. A case study involving Australian university lawyers reveals the 'program risks' of WIL. Program risk is a type of legal risk that relates to the conduct of universities, host organisations and students before, during and after a WIL placement, as well as the personal characteristics of students that can expose the university to legal risk. The research findings may be applied by university lawyers, academic disciplines and university management to evaluate and improve risk management in WIL programs.